2020
DOI: 10.1107/s1600576720005816
|View full text |Cite
|
Sign up to set email alerts
|

Near, far, wherever you are: simulations on the dose efficiency of holographic and ptychographic coherent imaging

Abstract: Different studies in X-ray microscopy have arrived at conflicting conclusions about the dose efficiency of imaging modes involving the recording of intensity distributions in the near (Fresnel regime) or far (Fraunhofer regime) field downstream of a specimen. A numerical study is presented on the dose efficiency of near-field holography, near-field ptychography and far-field ptychography, where ptychography involves multiple overlapping finite-sized illumination positions. Unlike what has been reported for coh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Phantom cell object (a) and limited-area coherent illumination spot [(b), the 'probe function'] used for our simulations. The 325 Â 325 pixel phantom cell is the same pure-phase object used in previous studies of the effect of changing photon fluence in different X-ray microscopy methods (Hagemann & Salditt, 2017;Du et al, 2020). The probe function's intensity is shown at the same scale here, but it is in fact a 72 Â 72 pixel array which is scanned across the phantom, with the boundaries of the probe array indicated by a green box.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Phantom cell object (a) and limited-area coherent illumination spot [(b), the 'probe function'] used for our simulations. The 325 Â 325 pixel phantom cell is the same pure-phase object used in previous studies of the effect of changing photon fluence in different X-ray microscopy methods (Hagemann & Salditt, 2017;Du et al, 2020). The probe function's intensity is shown at the same scale here, but it is in fact a 72 Â 72 pixel array which is scanned across the phantom, with the boundaries of the probe array indicated by a green box.…”
Section: Figurementioning
confidence: 99%
“…in this case. Prior studies (Du et al, 2020) have shown that one can then estimate the required fluence from…”
Section: Rangementioning
confidence: 99%
See 3 more Smart Citations